2011
DOI: 10.1177/0192623311413787
|View full text |Cite
|
Sign up to set email alerts
|

Nanomaterials in Humans

Abstract: Nanomaterials are increasingly being used for commercial purposes. However, concerns about the potential risks of exposure to humans have been raised. We previously reported unusual pulmonary disease and death in a group of patients with occupational exposure to spray paint. However, the nanoparticle and chemical composition of the exposure was not fully described. The present study aimed to isolate and identify the nanoparticles observed in the patients' biopsies and report the potential deleterious effects t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 69 publications
(20 citation statements)
references
References 30 publications
(65 reference statements)
0
20
0
Order By: Relevance
“…After eighteen months of the disease, the amount of nanoparticles found in the pulmonary cells and macrophages was lower, but fibrous SiO nanostructures with lengths around 70 nm were detected in the nucleus and cytoplasm of alveolar epithelial cells. [158] It is thought that the exposure to SiO NPs from aerosol paint may have contributed to the patients’ illnesses. Therefore, it is important to completely understand the issues underlying nanosystems prior to using them.…”
Section: Biocompatibility Assessment For Si and Sio Particlesmentioning
confidence: 99%
“…After eighteen months of the disease, the amount of nanoparticles found in the pulmonary cells and macrophages was lower, but fibrous SiO nanostructures with lengths around 70 nm were detected in the nucleus and cytoplasm of alveolar epithelial cells. [158] It is thought that the exposure to SiO NPs from aerosol paint may have contributed to the patients’ illnesses. Therefore, it is important to completely understand the issues underlying nanosystems prior to using them.…”
Section: Biocompatibility Assessment For Si and Sio Particlesmentioning
confidence: 99%
“…But in humans, very few studies are available. Song et al (Song et al, 2011 found silica nanoparticles in clinical samples from 7 patients suffering from lung injuries after an occupational exposure. But as these patients were exposed to other toxic substances than dust and polyacrylate nanoparticles no firm conclusion could be reached.…”
Section: Introductionmentioning
confidence: 96%
“…Some reports describing serious adverse effects of occupational exposure to ENMs have been published: These include several cases of rescue workers present at the World Trade Center in New York City after the tragic events of 9/11 (Aldrich et al, 2010; Gupta, 2011; NIOSH, 2011; Romano, 2011; Zeig-Owens et al, 2011), reports of occupational exposures to mixtures containing nanoparticles in factories in China and India (Jaakkola et al, 2011; Song et al, 2009), a case-report regarding a worker who inhaled an estimated gram of nickel nanoparticles over an approximate 90-minute period, and who died from adult respiratory distress syndrome (Phillips et al, 2010), the development of unusual pulmonary disease in workers exposed to silica nanoparticles (Song et al, 2011), and the development of toxic epidermal necrolysis-like dermatitis in a chemist exposed to high levels of intermediate or final products of dendrimers while performing dendrimer synthesis (Toyama et al, 2009). Finally, a recent occupational survey showed an association with mortality due to chronic obstructive pulmonary disease and to ischemic heart disease in a cohort of workers exposed to metalworking fluids containing a substantial amount of incidental nanoparticles (Eisen et al, 2011).…”
Section: Introductionmentioning
confidence: 99%